ANALISIS KESIAPAN PESERTA DIDIK DALAM PEMBELAJARAN MENGGUNAKAN MEDIA LITERASI DIGITAL KELAS VI SD - Dian Erlita Dian; Lindayani; Nurul Zikri Filina; Febry Fahreza; Nurjannah; Syah Mohd Hadiid Thaariq; Fetro Dola Syamsu (Jurnal Genta Mulia, 2026)
The purpose of this study is to evaluate the readiness of sixth-grade elementary school students to use digital literacy media in learning. This research is based on how digital literacy is very important to support 21st-century learning. The research method used is quantitative descriptive with data collection techniques through questionnaires, observation, and interviews. A total of thirty sixth-grade elementary school students were the subjects of the study. The results of the study indicate that the level of student readiness in various aspects, including access to technology, the ability to use digital devices, and their views on digital-based learning, ranges from moderate to high. However, limitations in supporting facilities and obstacles in important aspects of digital information utilization continue to arise. As a result, efforts are needed to improve students' digital literacy through the integration of more interactive learning media and ongoing training.